"They say it's because I'm migrainous. . ." Contested identities of students with invisible disabilities in medical consultations. (June 2022) - Sowińska, Agnieszka
The objective of this article is to explore the identity construction by students with invisible disabilities as disclosed in medical consultations at a university health center. In particular, I work on the assumption that analysing the discursive processes through which students with invisible disabilities construct, negotiate and resist their roles and identities may contribute to a better understanding of living and studying with an invisible condition. Taking a discourse analytic approach, I consider identity as a dynamic and negotiable process that takes place in specific interactional occasions. The findings have shown that these students sometimes construct contested identities as patients, students, or experts during medical consultations, responding to conflicting expectations of others and their own.